Quantitative evaluation of fast free-hand volumetric ultrasound - Nikolaev, Anton V.; Hansen, Hendrik H. G.; Maal, Thomas J. J.; van Alfen, Nens; de Korte, Chris L. (Frontiers in Physics, 2022)
Free-hand volumetric ultrasound (FVUS) facilitates 3D US imaging of large anatomical areas. However, this method is user-dependent and image quality, especially in the scan direction (elevational direction), depends on the number of US images acquired per distance unit. This might affect clinical decision making for example in quantitative ultrasound muscle imaging. This study addresses three goals. First, to determine quantitatively below which number of acquisitions per cm (acq/cm) image quality is affected: the acquisition limit. Second, to determine the translation speed used naturally by sonographers. Third, to demonstrate in vivo possible benefits of utilizing plane wave imaging for FVUS, so-called fast FVUS in order to boost translation speed while maintaining quantitative image information. Fast FVUS enables imaging at much higher framerates and hence the acquisition limit is easier met which allows for much faster transducer translation. From an analysis of the contrast and elevational resolution in a phantom, the average acquisition limit was determined to be 33 acq/cm. Above this limit, the quantitative ultrasound information remained unchanged. This would imply that when imaging at 30 frames per second, a common frame-rate of current 2D ultrasound devices, suboptimal imaging quality is obtained above transducer translation speeds of 9.1 mm/s. The median and maximum transducer translation speed observed in 10 sonographers were 15.8 mm/s and 30.1 mm/s, thus above this limit. Finally, we presented a design of fast FVUS that enabled acquiring 200 fps, and hence, would allow imaging up to speeds of 60.6 mm/s. We demonstrated in vivo in tibialis anterior muscles that more anatomical details were visible with fast FVUS which were lost at the typical framerate. These observations support our hypothesis that fast FVUS would be an ideal method for 3D quantitative muscle ultrasound.